The Performance of Differential Pressure (DP) and Inlet Temperature by Using Fabric Filter at Coal-Fired Power Station - Rasidah Binti Abdul Rani; Norsa'adah Binti Mahmor; Norazila Binti MD Posdzi; Wan Zaizul Adlan Bin Wan Zulkifli (Universitas Muhammadiyah Yogyakarta, 2023)
This paper presents the performance of differential pressure (DP) and inlet temperature by using fabric filter at Coal-Fired Power Station. A fabric filter is one of eco-friendly methods that popular application in the industry to cater and filter the flue gas that contained fly ashes, that been produced by combustion of pulverized coal inside the boiler furnace. This study focuses on analyse the reading of differential pressure and inlet temperature and determining condition of fabric filter. The evaluation of this result is to maintain the differential pressure at 14 – 18 mbar and inlet temperature at 130 0C. The performance of the fabric filter will be analysed using the monitoring report performance based on daily walkdown inspection and calibration schedule report. Based on the report results prove that the performance of fabric filter is in satisfactory condition and met with DOE requirements, which the flue gas within in 30 minutes observation only contain 150mg/m3 of ash. The protection of the system ensures the fabric filter in optimum condition.